2007
DOI: 10.1091/mbc.e06-06-0512
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Biogenesis Is Sensed at the Start Cell Cycle Checkpoint

Abstract: In the yeast Saccharomyces cerevisiae it has long been thought that cells must reach a critical cell size, called the “setpoint,” in order to allow the Start cell cycle transition. Recent evidence suggests that this setpoint is lowered when ribosome biogenesis is slowed. Here we present evidence that yeast can sense ribosome biogenesis independently of mature ribosome levels and protein synthetic capacity. Our results suggest that ribosome biogenesis directly promotes passage through Start through Whi5, the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 59 publications
(108 reference statements)
10
123
1
2
Order By: Relevance
“…Examples of cross talk between ribosome assembly and other cellular processes mediated through shared components include replication, rRNA transcription, tRNA export, cell cycle control, and stress response (e.g., Angermayr and Bandlow 2002;Du and Stillman 2002;Steiner-Mosonyi et al 2003;Killian et al 2004;Bernstein et al 2007;Rudra et al 2007;Strub et al 2007;Jwa et al 2008), and this cross talk is more evolved in higher organisms. Because the connection to the cell cycle has been recently and expertly reviewed (Dez and Tollervey 2004;, it will not be covered here.…”
Section: Cross Talk Of Ribosome Biogenesis Through Shared Componentsmentioning
confidence: 99%
“…Examples of cross talk between ribosome assembly and other cellular processes mediated through shared components include replication, rRNA transcription, tRNA export, cell cycle control, and stress response (e.g., Angermayr and Bandlow 2002;Du and Stillman 2002;Steiner-Mosonyi et al 2003;Killian et al 2004;Bernstein et al 2007;Rudra et al 2007;Strub et al 2007;Jwa et al 2008), and this cross talk is more evolved in higher organisms. Because the connection to the cell cycle has been recently and expertly reviewed (Dez and Tollervey 2004;, it will not be covered here.…”
Section: Cross Talk Of Ribosome Biogenesis Through Shared Componentsmentioning
confidence: 99%
“…8). Several studies in yeast and human cells have suggested a checkpoint control system that senses the cellular activity to newly synthesize ribosomes, independently of the level of pre-existing ribosomes (Oeffinger and Tollervey, 2003;Zhang et al, 2003;Bernstein et al, 2007). Another even more likely possibility, therefore, is that cells stalled in cell division when they were deficient in ribosome biogenesis in the absence of USP36.…”
Section: Cellular Function Of Usp36mentioning
confidence: 99%
“…[64][65][66] Conversely, because protein synthesis and growth is only desirable under favorable cellular conditions, ribosome synthesis is highly responsive to growth conditions, including nutrient availability, heat and cold shock, as well as oxidative stress. [67][68][69][70][71] The mechanisms underlying these regulatory steps are poorly understood.…”
Section: Integration Of Ribosome Assembly and Growthmentioning
confidence: 99%